Ultrasound in schistosomiasis mansoni - Rogério Augusto Pinto-Silva; Leonardo Campos de Queiroz; Letícia Martins Azeredo; Luciana Cristina dos Santos Silva; José Roberto Lambertucci (Memorias do Instituto Oswaldo Cruz, 2010)
We reviewed ultrasound features in patients with schistosomiasis mansoni. The alterations that we observed in acute and hepatosplenic schistosomiasis are described. The advantages and disadvantages of using ultrasound patterns in the evaluation of liver fibrosis are discussed. Other diseases that are important in the differential diagnosis of schistosomal liver fibrosis are presented. Ultrasound is an effective and flexible diagnostic tool in the evaluation of a variety of diseases. It presents no harmful effects to patients, allowing non-invasive studies in hospitalized patients and in other facilities.